PRODUKSI PEKTIN DARI KULIT BUAH COKLAT (Theobroma Cacao) (The production pectin from Cacao leather) - Edahwati, Luluk; MT, Susilowati; Harsini, Tutuk (UPN VETERAN JAWA TIMUR, 2011)
The progress and development of the industry in Indonesia is increasing demand for pectin. Indonesia is a country rich in agricultural crops, one of cacao. This cacao leather is the only waste that can not be used. In this study are described on the extraction of pectin from waste chocolate skin. Pectin is an important component in the food industry, cosmetics and medicines. The research using two variables, time (200,225,250,275,300 minutes),and the ratio of solvent (1:8,1; 10,1:12,1:16,1:16)l.The results obtained on the condition of the maximum time of 250 minutes and a solvent ratio of 1:12. The yield of weight of pectin was 16.23%Keywords : Cocoa skin, Pectin, extraction